HUBUNGAN AGAMA DAN NEGARA DALAM PERSPEKTIF PEMIKIRAN SAYYID QUTUB - Sarif Sarif (Manthiq, 2016)
Abstract: Religion Andstaterelations In The Perspectiveof  Sayyid Qutb. This paper  discusses the  main points  of Sayyid Qutb  thought  of religion  as  the  foundations of the  state  and  his  thoughts about  the relationship between religion and state.  This type of research is library researchby using literature  as the primary data  in the research, and studies are presented in descriptive analysis.  The method used  in this study is a qualitative  approach to history. From the  results  of this study found  that, according to Sayyid Qutb, religion must  be  the  basis  for the  formation of a government. For Sayyid Qutb, to obtain  the  title of an Islamic  government, a community or a country  should  be  run in accordance to the  rules  and  the laws of God. Furthermore, Sayyid Qutb mentioned three  aspects that can  be classified  as the principles of the  Islamic  government, namely  justice  authorities, the  obedience of the  people, and  deliberations between the  authorities and  the  people. Sayyid Qutb  also  recommended that  a political  power  in the state  must  be  in accordance with religious  teachings, because the  religion and  state  have  interlocking relationships.